Sub-molecular spectroscopy and temporary molecular charging of Ni-phthalocyanine on graphene with STM. Issue 29 (12th July 2018) - Zhao, Mali; Almarzouqi, Faisal; Duverger, Eric; Sonnet, Philippe; Dujardin, Gérald; Mayne, Andrew J.
Abstract : In this study, the self-assembled molecular network and electronic properties of Ni-phthalocyanine (NiPc) molecules on monolayer graphene (MLG)/6H-SiC(0001) were studied by room temperature Scanning Tunnelling Microscopy (STM) and Density Functional Theory (DFT) calculations. Abstract : In this study, the self-assembled molecular network and electronic properties of Ni-phthalocyanine (NiPc) molecules on monolayer graphene (MLG)/6H-SiC(0001) were studied by room temperature Scanning Tunnelling Microscopy (STM) and Density Functional Theory (DFT) calculations. In this study, a very weak electronic coupling between the graphene and the NiPc molecules is found. This is due to the very small charge transfer of only 0.035 e − per molecule. The weak molecule–graphene interaction has two observable consequences: sub-molecular resolution was obtained in the STM spectroscopy at room-temperature with the molecules adsorbed directly on the graphene, and the occupied and unoccupied molecular resonance peaks were observed to shift their position in energy as a function of the tip–surface distance. This is due to the temporary local charging (either positive or negative) that is achieved by decreasing the surface voltage under the STM tip. This may have important consequences for future studies of the opto-electronic properties of such hybrid graphene–molecule systems.